Three phase dispersive liquid-liquid microextraction (DLLME) based on reverse micelles for the enrichment of Q-markers of cinnamic acids in traditional Chinese medicine. Issue 6 (2nd November 2021) - Liu, Zhao-chan; Yang, Li; Xing, Rong-rong; Chen, Xuan; Bai, Xiao-hong; Hu, Shuang
Abstract: This work describes three phase dispersive liquid-liquid microextraction based on reverse micelles for the determination of Q-markers of cinnamic acids (caffeic acid, p -hydroxycinnamic acid, ferulic acid, and cinnamic acid) in traditional Chinese medicine followed by high performance liquid chromatography (HPLC) analysis. The variables influencing the procedure were optimized separately. Enrichment factors from 110 to 189, linearities from 1.2 to 960 ng mL −1 with r 2 exceeding 0.9943, detection limits from 0.1 to 0.6 ng mL −1, excellent precision with relative standard deviations below 5.6%, and good relative recoveries from 80.0% to 113.3% were achieved. In addition, the mechanism of the procedure was explored by comparison with conventional dispersive liquid-liquid microextraction at the optimum conditions. The results showed that the developed microextraction procedure improved the sensitivity and consumed less organic solvent and is a greener approach.